2008
DOI: 10.1002/smll.200700754
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Essential Micronutrients by Carbon Nanotubes and the Implications for Nanotoxicity Testing

Abstract: Hungry nanotubes: Single‐walled carbon nanotubes (SWNTs) compete with cells by interacting with folate and other essential micronutrients in cell culture medium (see picture). Sequestering of folate can cause apparent toxicity even without direct nanotube–cell contact through a new “starvation” mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(146 citation statements)
references
References 29 publications
(22 reference statements)
6
136
1
2
Order By: Relevance
“…As seen in previous studies, SWCNT with their large surface area can interact with a variety of organic molecules [Casey et al, 2007a,b;Casey et al, 2008;Guo et al, 2008] and have been shown to reduce TNF-α levels in culture medium by up to 20% in this study (see section on materials and methods). Therefore, decreased inflammatory mediator responses with increasing concentrations of SWCNT may also be due to decreased levels of TNF-α available for the cells due to binding if TNF-α onto SWCNT.…”
Section: Effects Of Particle Exposure On Rh-tnf-α Stimulated Cellssupporting
confidence: 76%
“…As seen in previous studies, SWCNT with their large surface area can interact with a variety of organic molecules [Casey et al, 2007a,b;Casey et al, 2008;Guo et al, 2008] and have been shown to reduce TNF-α levels in culture medium by up to 20% in this study (see section on materials and methods). Therefore, decreased inflammatory mediator responses with increasing concentrations of SWCNT may also be due to decreased levels of TNF-α available for the cells due to binding if TNF-α onto SWCNT.…”
Section: Effects Of Particle Exposure On Rh-tnf-α Stimulated Cellssupporting
confidence: 76%
“…The results show that protein charge and size are paramount for the interaction with CNT, likewise CNT surface functional groups and the surface area available for interaction. Smaller, positive charged particles are more likely to bind in significant amounts to both functionalized and non-functionalized CNT, as the present results suggest, and in agreement with the conclusions from previous studies (Guo et al, 2008). Functionalizing CNT may further enhance adsorption.…”
Section: Mechanisms Of Interaction Of Cntsupporting
confidence: 93%
“…This implies that indirect mechanisms of toxicity may influence the results of in vitro studies, since some of these molecules are essential for cell viability and proliferation. SWCNT cause dose-dependent adsorption of culture medium amino acids and vitamins, showing higher affinity for planar aromatic or conjugated structures, and for positively charged solutes (Guo et al, 2008). Functionalization of SWCNT and MWCNT with terminal or surface specific groups alters solubility and protein adsorption, including of cytokines IL6 and IL8, in a dose-dependent manner (Tian et al, 2006).…”
Section: Mechanisms Of Interaction Of Cntmentioning
confidence: 99%
“…The exact mechanism responsible for the changes in the expression levels of these 14 proteins is not clear. It is thought that the direct interaction of the cells with MWCNTs and CNTs induces indirect cytotoxicity (Casey et al, 2008;Guo et al, 2008). Guo et al found that SWCNTs adsorb folate and that the resulting folate deficiency reduces viability.…”
Section: Discussionmentioning
confidence: 99%